If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1) + 12 + 2x = 6x + -40 + 2(30 + -1x) + -2 Reorder the terms: 4(-1 + x) + 12 + 2x = 6x + -40 + 2(30 + -1x) + -2 (-1 * 4 + x * 4) + 12 + 2x = 6x + -40 + 2(30 + -1x) + -2 (-4 + 4x) + 12 + 2x = 6x + -40 + 2(30 + -1x) + -2 Reorder the terms: -4 + 12 + 4x + 2x = 6x + -40 + 2(30 + -1x) + -2 Combine like terms: -4 + 12 = 8 8 + 4x + 2x = 6x + -40 + 2(30 + -1x) + -2 Combine like terms: 4x + 2x = 6x 8 + 6x = 6x + -40 + 2(30 + -1x) + -2 8 + 6x = 6x + -40 + (30 * 2 + -1x * 2) + -2 8 + 6x = 6x + -40 + (60 + -2x) + -2 Reorder the terms: 8 + 6x = -40 + 60 + -2 + 6x + -2x Combine like terms: -40 + 60 = 20 8 + 6x = 20 + -2 + 6x + -2x Combine like terms: 20 + -2 = 18 8 + 6x = 18 + 6x + -2x Combine like terms: 6x + -2x = 4x 8 + 6x = 18 + 4x Solving 8 + 6x = 18 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 8 + 6x + -4x = 18 + 4x + -4x Combine like terms: 6x + -4x = 2x 8 + 2x = 18 + 4x + -4x Combine like terms: 4x + -4x = 0 8 + 2x = 18 + 0 8 + 2x = 18 Add '-8' to each side of the equation. 8 + -8 + 2x = 18 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 18 + -8 2x = 18 + -8 Combine like terms: 18 + -8 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| 6+4(x+2)+2x-3=2x+27 | | 4(x+3)+x=11 | | 7x-13=59-5x | | 9x-3=2x+11 | | 6x+3-2x-1=14 | | 12+6x-3+x+7-3x=32 | | 7w^2+6w+7=0 | | 4s^2-15s+9=0 | | -11+(-10)= | | 6(t-3)+8t=7(2t+3)-13 | | 0=26 | | 1+-6= | | 7x-3=4.5 | | 0.5(5x+8)=0.5x | | x^2-12x+36=4x+4 | | 3(x+8)=1+3x | | 0.125(x-16)=0 | | 2w^2+5w-3=0 | | 7d-3d+6d+3=3d | | 0.25x-1=1 | | 4x^2-8x+0=0 | | 0.33x-5=3 | | 0.33x=8 | | 0.5x=8 | | 10x-=7x+17 | | 3a^2+20a+40=0 | | x^2+100x+256=0 | | 2x+3=2(-1+3x) | | 3x+11=-7x-5 | | 6v^2+7-10= | | -2x^2-7x+3=0 | | 10x^2+3x=0 |